Financial frictions,the Phillips curve and monetary policy - Lieberknecht, Philipp (Deutsche Bundesbank, 2019)
This paper proposes a tractable financial accelerator New Keynesian DSGE modelthat allows for closed-form solutions. In the presence of financial frictions, theNew Keynesian Phillips curve features a flat slope with respect to the output gapand is strongly forward-looking. All shocks cause endogenous cost-push effects inthe Phillips curve, leading to larger inflation responses and a breakdown of divinecoincidence. The central bank's contemporaneous trade-off between output gap andinflation stabilization is aggravated. Optimal monetary policy is strongly forward-looking and geared towards inflation stabilization.
10419/213075
Keywords: Graue Literatur; Financial frictions; financial accelerator; Phillips curve; optimal monetary policy